The Use of Primers Heavily Labeled with Fluorescein in Polymerase Chain Reaction - Ptitsyn, K.G.; Khmeleva, S.A.; Kurbatov, L.K.; Suprun, E.V.; Radko, S.P. (Biomedical Chemistry: Research and Methods, 2023)
The fluorescently-labeled DNA is widely used in various bioanalytical applications. For a number of applications, a high level of labeling could be beneficial. One of the ways to produce DNA fragments bearing multiple fluorescent tags is to use polymerase chain reaction (PCR) with primers heavily labeled with fluorophores. Here we tested how primers with multiple fluorescein tags perform in PCR. It has been found that the positioning of fluorescein tags at or near the 3′-end upon primer multiple labeling can inhibit DNA amplification (up to a complete stop when tags are placed at the 3′- or adjacent nucleotide). The mechanism, by which the presence of fluorescein tags at or near the primer 3′-end affects the PCR performance, is rather ambiguous and can involve both a steric hindrance for polymerase binding from the fluorescein moiety, as well as destabilization of a primer-template duplex. Nonetheless, if multiple fluorescein tags are attached so that at least three nucleotides from the primer 3′-end are unmodified, the production of DNA fragments bearing multiple fluorescein molecules is possible even if both primers are heavily labeled, though on the expense of amplicon yield.